1965
DOI: 10.1172/jci105159
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surface Activity in Induced Pulmonary Edema*

Abstract: Induction of acute pulmonary edema in anesthetized dogs causes a large fall in compliance. out of proportion to lung volume (1), and a sharp increase in venous admixture that can be reversed by forcible inflation of the lungs (2). This pattern of abnormal function suggested alveolar closure (1, 2).Since alveolar stability depends in large measure on the presence of normal pulmonary surface properties (3), altered surface forces were consiclered as an underlying mechanism. Cook and co-workers (1) reasoned that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1966
1966
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 15 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…Although the nature of the forces responsible for this pericapillary pressure is not entirely clear, it seems that surface tension at the alveolar air-fluid interface may be involved (20). In particular, in the group II experiments of the present study, the heightened surface tension that occurs as fluid accumulates in alveoli (11,12) may, in turn, have contributed to the formation of edema.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although the nature of the forces responsible for this pericapillary pressure is not entirely clear, it seems that surface tension at the alveolar air-fluid interface may be involved (20). In particular, in the group II experiments of the present study, the heightened surface tension that occurs as fluid accumulates in alveoli (11,12) may, in turn, have contributed to the formation of edema.…”
Section: Introductionmentioning
confidence: 59%
“…2) The force exerted by surface tension at the pulmonary air-fluid interface, which presumably affects pericapillary (and therefore transcapillary) pressure (10), would be expected to change progressively during pulmonary edema (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in contrast to a hyperoxia study in the neonatal rat (24) which has reported no change in the air deflation PV curve in rats exposed to 80% oxygen for 6 d and decreased compliance in rats exposed to >95% oxygen; however, the lungs were degassed before measurement. The increased compliance in the air PV deflation curve of our 80% oxygen exposed neonatal mice may be due to a stiffening of lung tissue by collagen deposits or to edema, which could increase the tendency for alveolar collapse and lung recoil with lowering of distending pressure (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…of the alveolar epithelium, and contamination of the alveolar spaces with protein-rich material that inhibits the surface activity. It was suggested more than a decade ago that surfactant inhibition occurs (28), and recent evidence indicates that surfactant is inhibited in immature lambs (15) treated with exogeneous surfactant, oxygen and artificial ventilation. Our data demonstrate that similar inhibition can occur in mature rat lungs, despite apparently normal surfactant phospholipids.…”
Section: Discussionmentioning
confidence: 99%